2002
DOI: 10.1248/cpb.50.515
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Inhibitory Constituents from Duranta repens.

Abstract: The genus Duranta (Verbenaceae) comprises about 35 species which are distributed in tropical and sub-tropical regions. The literature survey revealed that very little phytochemical work has been carried out on the genus Duranta, and only some steroids, 1) triterpenes 2) and iridoids 3) have so far been reported. Duranta repens LINN. is widely distributed in northern parts of Pakistan and finds various medicinal uses in the indigenous system of medicine. The fruits of this plant afford a medicine for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The MeOH extract of the plant also shows insecticidal and antifeedant properties against Aedes aegypti and Attagenus piceus, respectively 4 . Previous studies on the genus Duranta have resulted in the isolation of various compounds, including coumarinolignoids 5 , (E)-cinnamic acid, (E)-p-methoxycinnamic acid 6 , diterpenoids 7,8 , flavonoids 7,8 , steroids 9 , glycosides of phenylpropanoids 10,11 , triterpenes 12 , and iridoids 6,13,14 . Malaria is one of the most common infectious diseases in tropical and subtropical countries, including parts of the Americas, Asia, and Africa.…”
Section: Duranta Repens Linn (Syn D Erecta D Microphylla D Plumentioning
confidence: 99%
See 1 more Smart Citation
“…The MeOH extract of the plant also shows insecticidal and antifeedant properties against Aedes aegypti and Attagenus piceus, respectively 4 . Previous studies on the genus Duranta have resulted in the isolation of various compounds, including coumarinolignoids 5 , (E)-cinnamic acid, (E)-p-methoxycinnamic acid 6 , diterpenoids 7,8 , flavonoids 7,8 , steroids 9 , glycosides of phenylpropanoids 10,11 , triterpenes 12 , and iridoids 6,13,14 . Malaria is one of the most common infectious diseases in tropical and subtropical countries, including parts of the Americas, Asia, and Africa.…”
Section: Duranta Repens Linn (Syn D Erecta D Microphylla D Plumentioning
confidence: 99%
“…The structures of the known compounds (3-7) were established by comparison of their spectral data with literature values 7,8,20 . The two new flavonoid glycosides (1, 2) and the known flavonoids (3-7) described in this study were tested for anti-plasmodial activities against the chloroquine-sensitive (D6) and chloroquine-resistant (W2) strains of Plasmodium falciparum.…”
mentioning
confidence: 99%
“…Duranta repens also known as yellow bush (the leaves) or pigeon berry (the seeds) is a fast growing, large, spreading shrub with numerous stems that reaches a height of 1-3 m (Okunlola, 2013). It belongs to the Verbenaceae family with the genus Duranta made up of about 35 species (Anis et al, 2002). Rowezak (2001) suggested that the fragrant pale blue flowers coupled to the golden orange berries make the plant appear very attractive.…”
Section: Introductionmentioning
confidence: 99%
“…11 Low molecular weight inhibitors of PEP have been reported in the literature, but the majority of these are of synthetic origin. In turn most of the natural PEP inhibitors are of microbial origin.…”
mentioning
confidence: 99%